Advanced Materials Research. VII : 8th International Conference on Advanced Materials Research (ICAMR-2018) - Zhuiykov, Serge (Trans Tech Publications, 2018)
This collection is based on articles describing the last results of the scientific and engineering researches in the area of materials science and materials processing technologies that were presented at the 8th International Conference on Advanced Materials Research (ICAMR-2018, January 20-22, 2018, Fukuoka, Japan). We hope that these research results will be useful for many readers whose activities relate to the development of modern materials and processing technologies Ceramics, Composites, Polymers, Semiconductors, Functional Materials, Nanomaterials, Nanotechnologies, Steel, Alloys, Materials Processing, Building Materials, Chemical Technologies Materials Science.